Vapochromic Behaviors of A Solid‐State Supramolecular Polymer Based on Exo‐Wall Complexation of Perethylated Pillar[5]arene with 1, 2, 4, 5‐Tetracyanobenzene. Issue 15 (3rd March 2021) - Wang, Mengbin; Li, Qing; Li, Errui; Liu, Jiyong; Zhou, Jiong; Huang, Feihe
Abstract: The research for the solid‐state supramolecular polymers with specific functions accelerates the development of supramolecular and materials sciences. Herein, we discover the different complexation modes of perethylated pillar[5]arene (EtP5 ) with 1, 2, 4, 5‐tetracyanobenzene (TCNB ) in various solvents. Driven by charge‐transfer interaction, TCNB is enclosed in the cavity of EtP5 in CHCl3, while TCNB complexes with EtP5 at the exo‐wall of EtP5 in CH2 Cl2 . This is because the size of CH2 Cl2 matches the cavity of EtP5, forcing TCNB to complex with the exo‐wall of EtP5 . Furthermore, we fabricate a vapochromic solid‐state supramolecular polymer by exploiting the exo‐wall complexation, which turns from brown to reddish brown or black after adsorption of alkyl aldehyde vapors. The adsorptive nature for alkyl aldehyde vapors comes from the unoccupied cavity of EtP5 based on C−H⋅⋅⋅π interactions. The vapochromic property is attributed to the change of the charge‐transfer interaction caused by molecular rearrangement induced by vapor‐capture in the solid‐state supramolecular polymer. Abstract : A vapochromic solid‐state supramolecular polymer is constructed based on the exo‐wall complexation between perethylated pillar[5]arene and 1, 2, 4, 5‐tetracyanobenzene. It changes its color from brown to reddish brown or black after adsorption of CH2 Cl2 and aldehyde vapors. This vapochromic property is attributed to the change of charge‐transfer interaction between these two compounds caused by the molecular rearrangement induced by vapor capture.